A Study of Tourism Revenue Multipliers and Leakage Affecting Sustainable Community Incomes: A Case Study of Sai Noi Homestay Ecotourism Village, Phra Nakhon Si Ayutthaya Province, Thailand - Nonthasorn , Sarika; Phansaita , Nalinee; Prougestaporn , Atthawet (Journal of Applied Economics and Management Strategy, 2025)
This mixed-method research was conducted in two phases with four main objectives. Phase 1 employed quantitative methods to analyze tourism income data from 2020 to 2022, aiming to: 1) analyze tourism multipliers affecting residents’ income, 2) study income leakage in the tourism community through input-output models, and 3) examine community members’ savings behavior. Survey data were collected from 25 key community stakeholders, including local leaders and tourism-related operators. Phase 2 utilized qualitative methods, including interviews and group discussions with 6 community stakeholders, to 4) develop sustainable recommendations for increasing tourism income. Data analysis included input-output modeling, multiplier and leakage calculations, descriptive statistics, and content analysis. Results showed the village’s income multiplier of 1.7194 generated an economic impact of 7,970,490 baht from tourism. This indicates significant economic benefits received by the village from tourism in terms of high monetary benefits. Tourist spending produced more direct than indirect income, with food and beverage services generating the highest revenue. The production activities’ leakage multiplier of 1.0541 resulted in a total income leakage of 259,360 baht, with 53.88% from food and beverage services. The average propensity to save (APS) of 0.1204 indicated villagers’ income exceeded consumption spending, enabling savings primarily through savings bonds and Government Savings Bank bonds for emergencies. Recommendations for increasing sustainable tourism revenue focused on four areas: 1) community-based tourism management, 2) community engagement, 3) tourism resources, and 4) economics and supply chain management within the community.